A New Homotetramer Hemoglobin in the Pulmonary Surfactant of Plateau Zokors (Myospalax Baileyi) - Li, Jimei; An, Zhifang; Wei, Linna; Xu, Bo; Wang, Zhijie; Gao, Conghui; Wei, Lian; Qi, Delin; Shi, Peng; Zhang, Tongzuo; Wei, Dengbang (Frontiers in Genetics, 2022)
The plateau zokor (Myospalax baileyi) is a native species to the Qinghai-Tibetan Plateau, inhabiting in hypoxia and hypercapnia sealed subterranean burrows that pose several unique physiological challenges. In this study, we observed a novel heme-containing protein in the pulmonary surfactant (PS) of plateau zokor, identified the encoding gene of the protein, predicted its origination and structure, verified its expression in alveolar epithelial cells, and determined the protein’s affinity to oxygen and its effect on the oxygen-dissolving capability in PS of plateau zokors. The protein is a unusual homotetramer hemoglobin that consisting of four γ-like subunits, and the subunit is encoded by a paralog gene of γ, that is γ-like. The divergence time of γ-like from γ is estimated by the molecular clock to be about 2.45 Mya. The generation of γ-like in plateau pikas might well relate to long time stress of the high land hypoxia. Unlike γ, the γ-like has a hypoxia response element (HRE) and a lung tissue-specific enhancer in its upstream region, and it is expressed specifically in the lung tissues and up-regulated by hypoxia. The protein is named as γ4-like which is expressed specifically in II type epithelial cells (ATII) and secreted into the alveolar cavities through the osmiophilic multilamellar body (LBs). The γ4-like has higher affinity to oxygen, and that increases significantly oxygen-dissolving capability in PS of plateau zokors by its oxygenation function, which might be likely to have beneficial for the plateau zokors to obtain oxygen from the severe hypoxia environments by facilitating oxygen diffusion from alveoli to blood.